Field-testing the Euro-MCD Instrument: Experienced outcomes of moral case deliberation. (March 2020) - de Snoo-Trimp, Janine C; Molewijk, Bert; Ursin, Gøril; Brinchmann, Berit Støre; Widdershoven, Guy AM; de Vet, Henrica CW; Svantesson, Mia
Background: Moral case deliberation is a form of clinical ethics support to help healthcare professionals in dealing with ethically difficult situations. There is a lack of evidence about what outcomes healthcare professionals experience in daily practice after moral case deliberations. The Euro-MCD Instrument was developed to measure outcomes, based on the literature, a Delphi panel, and content validity testing. To examine relevance of items and adequateness of domains, a field study is needed. Aim: To describe experienced outcomes after participating in a series of moral case deliberations, both during sessions and in daily practice, and to explore correlations between items to further validate the Euro-MCD Instrument. Methods: In Sweden, the Netherlands, and Norway, healthcare institutions that planned a series of moral case deliberations were invited. Closed responses were quantitatively analyzed. The factor structure of the instrument was tested using exploratory factor analyses. Ethical considerations: The study was approved in Sweden by a review board. In Norway and the Netherlands, data services and review boards were informed about the study. Results: The Euro-MCD Instrument was completed by 443 and 247 healthcare professionals after four and eight moral case deliberations, respectively. They experienced especially outcomes related to a better collaboration with co-workers and outcomes about individual moral reflexivity and attitude, both during sessions and in daily practice. Outcomes were experienced to a higher extent during sessions than in daily practice . The factor structure revealed four domains of outcomes, which did not confirm the six Euro-MCD domains. Conclusion: Field-testing the Euro-MCD Instrument showed the most frequently experienced outcomes and which outcomes correlated with each other. When revising the instrument, domains should be reconsidered, combined with theory about underlying concepts. In the future, a feasible and valid instrument will be presented to get insight into how moral case deliberation supports and improves healthcare.